FROM LITERACY TO FINANCIAL EDUCATION: A SURVEY OF METHODS TO MEASURE PHENOMENA. THE PARTICULAR SITUATION OF ROMANIA - SOCOL, Adela (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
People with a high level of financial literacy represent a premise for the societies' evolution and wellbeing, because informed citizens are capable to manage their money, to take proper financial decisions and to contribute to general prosperity and financial stability. We analysed the ideological acceptations of the basic concepts and the methodology of measuring financial literacy. The paper emphasizes on the problem of low financial literacy across countries. This problem could be solved by developing a national strategy of financial education that is the premise for efficient financial education.